2010
DOI: 10.1016/j.ajic.2009.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Health care workers' views about respirator use and features that should be included in the next generation of respirators

Abstract: To increase substantially the acceptance of respiratory protective equipment and improve compliance rates, respirators should be modified to meet the specific needs of health care workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
113
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(121 citation statements)
references
References 39 publications
4
113
0
4
Order By: Relevance
“…Interestingly, there was only one subject who mentioned the presence of moisture, a characteristic that has been reported as a major deterrent to respirator use. (22) This tends to agree with observations from the Roberge et al (23) study that found only minimal moisture (∼0.10 g) was retained on an N95 FFR after a subject's walking on a treadmill for an hour while wearing a respirator. However, given that the subjects only wore the FFR for ∼ 30 min in this study, this finding may not be surprising.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, there was only one subject who mentioned the presence of moisture, a characteristic that has been reported as a major deterrent to respirator use. (22) This tends to agree with observations from the Roberge et al (23) study that found only minimal moisture (∼0.10 g) was retained on an N95 FFR after a subject's walking on a treadmill for an hour while wearing a respirator. However, given that the subjects only wore the FFR for ∼ 30 min in this study, this finding may not be surprising.…”
Section: Discussionsupporting
confidence: 89%
“…Multiple studies have demonstrated that HCWs, in general, comply poorly with respiratory protection guidelines, especially when a N95 respirator is recommended 24 . However, a recently published randomized Canadian study demonstrated that the incidence of laboratory‐confirmed influenza was similar in HCWs wearing a surgical mask compared with HCWs wearing a N95 mask 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Results of a recent survey of health care workers indicated that improved compliance might be observed with more comfortable respirators that diminish heat buildup and interfere less with breathing. (35) …”
Section: Respiratory Protection Implicationsmentioning
confidence: 99%